Adequate Silicone Oil Tamponade by Utilizing the Space of Anterior Segment for Complicated Retinal Detachment: Technique, Efficacy, and Safety. Issue 6 (November 2021) - Wang, Yifan; Huang, Zijing; Zheng, Dezhi; Liu, Juntao; Huang, Dingguo; Zheng, Jianlong; Xie, Haixia; Lin, Peimin; Chen, Weiqi
Abstract : Purpose: To evaluate the efficacy and safety of adequate silicone oil (SO) tamponade procedure in patients with complicated retinal detachment. Methods: Thirty-one eyes in 31 patients were enrolled in this prospective case series. Adequate SO tamponade was performed by injecting the SO into the vitreous cavity and the entire anterior chamber, followed by posterior capsulotomy and inferior peripheral iridotomy. Preoperative and follow-up data including retinal anatomic reattachment and SO status, best-corrected visual acuity, intraocular pressure, surgical complications and management were collected and analyzed. Results: Twenty-nine eyes presented with complete retinal reattachment after subsequent SO removal with a primary success rate of 93.5%. Seventeen patients (54.8%) had complete anterior chamber SO migration to the vitreous cavity within the first postoperative day. The average time for anterior chamber SO migration was 2.3 ± 1.8 days. No oil-fluid interface in the vitreous cavity was observed in all the eyes, indicating a relatively adequate SO tamponade. Acute intraocular pressure elevation occurred in 16 (51.6%) eyes and was controllable under medication (n = 16) and anterior chamber paracentesis (n = 1). Two patients developed recurrent retinal detachment and received SO removal and a secondary adequate SO tamponade. At final follow-up, all the eyes had SO removal for at least 3 months and retinas maintained completely attached. Conclusions: The adequate SO tamponade procedure offers a simple, safe, and efficacious treatment alternative for complicated retinal detachment. Abstract : Supplemental Digital Content is available in the text